Nanodispersed Zn—MoO3 catalysts of selective ethanol oxidation synthesized by nontraditional methods - Sachuk, O.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The main features of transformations in the oxide ZnO—MoO3 = 1 : 1 composition under the action of ultrasonic (UST) and mechanochemical (MChT) treatments are established. The studies of modified samples demonstrate changes in the crystal structure of oxides, morphology of their surface, porous structure, and particle size (up to 13 nm), which stimulate the formation of new compounds directly in the processes of MCh and US treatments. The possibility of a simple formation of nanodispersed α- and β-phases of zinc molybdate ZnMoO4 in the form of needles and rods under the ultrasonic and mechanochemical activation, respectively, and the effectiveness of using these nontraditional methods to obtain highly active and selective zinc-molybdenum catalysts are shown. The high catalytic activity of the synthesized samples in the reaction of selective oxidation of ethanol to acetic aldehyde at 205 °C with a maximum yield of 94-96 % for this product is established.